D-Xylonic acid from recombinant e. coli BL21 (DE3): Comparison between shake flask and benchtop bioreactor fermentation - Nurul Atikah, Mohd Rodzri; Salwani, Md Zain; Rafidah, Mohamed Ali Hanapiah; Rozaimi, Abu Samah; R. M., Illias (IOP Publishing, 2020)
Production ᴅ-xylonic acid from recombinant E. coli BL21 (DE3) at a small scale has been successfully done several times. In an attempt to scale up the production process to a bigger scale, fermentation in bioreactor was conducted. The comparison on growth of recombinant E. coli BL21 (DE3) and production of ᴅ-xylonic acid in both shake flask and bioreactor was investigated. Higher specific growth rate of recombinant E. coli BL21 (DE3) and concentration of ᴅ-xylonic acid however, was obtained by fermentation in shake flask which is 0.273 h-1 and 9.06 gL-1 ᴅ-xylonic acid respectively. The result suggests several mistakes done during fermentation in bioreactor that causes low concentration of ᴅ-xylonic acid in bioreactor fermentation. Therefore, this calls up for improvement and better scale-up strategies in future work.